Muhammadiyah Sebagai Gerakan Pendidikan: Sejarah Eksistensi Perguruan Tinggi Muhammadiyah di Sulawesi Tenggara - Alifuddin, Muhammad (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2021)
This article presents an analytical description of the Muhammadiyah movement in the field of higher education services in Southeast Sulawesi. Data was garnered from in-depth interviews, observations and documents which were analyzed through the stages of data reduction, data presentation and drawing conclusions. The results of data analysis show that there are two main factors that move Muhammadiyah to establish universities in Southeast Sulawesi. First, internal factors such as moral awareness to build civilization through education. Second, external factors such as situational "pragmatic" dimensions and the influence of geo-political dimensions. This study shows that the success of Muhammadiyah in establishing universities is closely related to the collegial collective character and the strength of Muhammadiyah's philanthropic ethos. The large network of Muhammadiyah universities makes this organ gains social legitimacy as a reliable and trusted organ in higher education governance. The capital of cultural strength and social networks by Muhammadiyah activists is mobilized intelligently through elegant framing, so that in the end this organ is not only able to establish and build but also can advance higher education in a sustainable manner.Keywords: Higher education; Muhammadiyah; social movement theory